Kreativitas Dan Inovasi Terhadap Keberhasilan Usaha Kecil Dan Menengah (UKM) - Yasin, Nurfatwa Andriani; Insan, A Nur; Jumriah, Jumriah (Jurnal Online Manajemen ELPEI, 2025)
This study aims to examine the influence of creativity and innovation on the success of Small and Medium Enterprises in Makassar City. The sample in this study was 100 SMEs engaged in the culinary sector, which were recorded at the Makassar City Cooperative and SME Service. This study found that there was a positive and significant influence of creativity and innovation on the success of culinary SMEs in Makassar City. The largest correlation of creativity and innovation indicators is market trend adjustment with a value of 0.861, then strategy development with a value of 0.813, and finally the product variation indicator with a value of 0.743. These findings indicate that creativity and innovation have a positive and significant influence on the success of culinary SMEs in Makassar City. These two factors greatly help SMEs to be more adaptive in increasing competitiveness and achieving long-term growth.